Antithrombotic Activity and Hemolysis Pattern of Fibrinolytic Protease-Producing Bacterial Isolates from the Coast of Tanjung Dewa, South Kalimantan - Lutpiatina, Leka; Dwiyanti, Ratih Dewi; Insana, Aima; Rizal, Muhammad; Mufid, Muhammad (Medical Laboratory Technology Journal, 2025)
Cardiovascular disease is a leading cause of death worldwide, with thrombosis playing a key role in the pathological process. Conventional antithrombotic therapy often causes side effects, necessitating alternatives based on biological resources. Marine microorganisms are known to produce fibrinolytic protease enzymes that can degrade fibrin and prevent blood clot formation. This study aimed to evaluate the differences in antithrombotic activity and hemolysis patterns of fibrinolytic protease-producing bacterial isolates obtained from the coast of Tanjung Dewa Beach, South Kalimantan. A total of 15 isolates were obtained from seawater, beach sand, mollusks, crabs, and barnacles, and then subjected to colony morphology identification, Gram staining, and spore observation. Proteolytic activity testing using Skim Milk Agar media showed that all isolates had proteolytic activity with varying indices, with PSR1 showing the highest index (3.4). Furthermore, fibrinolytic testing using the fibrin plate assay method showed that 10 isolates were capable of degrading fibrin, with AL8 and SP2 showing the highest fibrinolytic indices (3.12 and 3.11, respectively). Antithrombotic testing using the clot lysis method revealed that AL7 and SP1 exhibited the highest lysis percentages (82.05% and 88.88%, respectively). Anticoagulant activity, as determined by the Lee-White method, showed that SP2 significantly prolonged the coagulation time (142 seconds, 49.65%). Hemolysis pattern testing revealed variations in activity, with AL8 and PSR1 classified as gamma-hemolytic and therefore potentially safer. Statistical analysis showed no significant differences between isolates in terms of antithrombotic activity, anticoagulant activity, or hemolysis pattern (p > 0.05). These findings suggest that coastal bacterial isolates from Tanjung Dewa Beach, particularly AL8 and SP2, have the potential to serve as safe, natural antithrombotic agents, supporting the development of biomedical therapies for cardiovascular disease.